2018
DOI: 10.1002/2017gb005753
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Biological Functioning Important for Simulating and Stabilizing Ocean Biogeochemistry

Abstract: The biogeochemistry of the ocean exerts a strong influence on the climate by modulating atmospheric greenhouse gases. In turn, ocean biogeochemistry depends on numerous physical and biological processes that change over space and time. Accurately simulating these processes is fundamental for accurately simulating the ocean's role within the climate. However, our simulation of these processes is often simplistic, despite a growing understanding of underlying biological dynamics. Here we explore how new paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 137 publications
0
16
0
Order By: Relevance
“…This type of non-Redfieldian dynamics was applied in the model used in Eggleston and Galbraith (2018) and Galbraith and de Lavergne (2018), but their results were not analysed in terms of difference from a Redfield model version. In addition, Buchanan et al (2018) explored the importance of dynamic response of ocean biology, such as flexible stoichiometry, for modelled ocean biogeochemistry in pre-industrial simulations. They found that the dynamic response was fundamental for stabilizing the response of ocean dissolved inorganic carbon (DIC) to changes in the physical circulation state.…”
Section: Introductionmentioning
confidence: 99%
“…This type of non-Redfieldian dynamics was applied in the model used in Eggleston and Galbraith (2018) and Galbraith and de Lavergne (2018), but their results were not analysed in terms of difference from a Redfield model version. In addition, Buchanan et al (2018) explored the importance of dynamic response of ocean biology, such as flexible stoichiometry, for modelled ocean biogeochemistry in pre-industrial simulations. They found that the dynamic response was fundamental for stabilizing the response of ocean dissolved inorganic carbon (DIC) to changes in the physical circulation state.…”
Section: Introductionmentioning
confidence: 99%
“…For example phosphate concentrations are systematically overestimated in the surface (Martiny et al, 2019a) and the global distribution of nitrogen fixation, denitrification, and oxygen minimum zones exhibit substantial variability between models (Fu et al, 2018). Recent global biogeochemical models are therefore starting to incorporate a more realistic representation of plankton physiology, which includes flexible phytoplankton C:N:P (e.g., Buchanan et al, 2018). Modeling studies with flexible phytoplankton stoichiometry have demonstrated that proliferation of C-rich phytoplankton under future climate scenario has the potential to buffer expected future decline in carbon export and net primary productivity caused by increased stratification (Kwiatkowski et al, 2018;Tanioka and Matsumoto, 2017).…”
mentioning
confidence: 99%
“…CSIRO Mk3L-COAL adequately reproduces the large-scale thermohaline properties and circulation of the ocean under preindustrial conditions in numerous prior studies (Phipps et al, 2013;Matear and Lenton, 2014;Buchanan et al, 2016Buchanan et al, , 2018.…”
Section: Model Performancementioning
confidence: 76%
“…evaporation). Because fractionation against one isotope relative to the other is miniscule, the isotopic content of a sample is conventionally expressed as a δ value (δ h E), where the ratio of the heavy to light element in solution ( h E: l E) is compared to a standard ratio ( h E std : l E std ) Previous versions of the OBGCM have explored changes in oceanic properties under past (Buchanan et al, 2016), present (Buchanan et al, 2018) and future scenarios Lenton, 2014, 2018). These studies have shown that the model can realistically reproduce the global carbon cycle, nutrient cycling and organic matter cycling in the ocean.…”
Section: Introductionmentioning
confidence: 99%